1999
DOI: 10.1021/ma981921l
|View full text |Cite
|
Sign up to set email alerts
|

Ring Structure of Cyclic Poly(2-vinylpyridine) Proved by Pyrolysis−GC/MS

Abstract: Poly(2-vinylpyridine) (P2VP) with cyclic structure was tentatively prepared through the reaction of linear P2VP having two living ends followed by coupling with a bifunctional coupling agent. Thus, prepared crude product was fractionated by preparative size exclusion chromatography in order to enrich the cyclic polymer portion. Then the existence of the ring structure in the fractionated P2VP sample was directly confirmed for the first time by pyrolysis-gas chromatography/mass spectrometry by detecting the cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 11 publications
1
27
0
Order By: Relevance
“…The detailed synthetic procedure of I was followed by the same manners as reported by Hayashi et al, 36 and the purification of I was in the same ways as reported previously. 31,35,37 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed synthetic procedure of I was followed by the same manners as reported by Hayashi et al, 36 and the purification of I was in the same ways as reported previously. 31,35,37 …”
Section: Methodsmentioning
confidence: 99%
“…Only for the low molecular weight cyclic polymers, the detailed cyclic structures were directly confirmed by NMR analysis of linking points, 22,23 pyrolysis-gas chromatography/mass spectrometry (Py-GC/MS), 31 and matrix-assisted laser desorption/ionization timeof-flight (MALDI-TOF) mass spectrometry.…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been devoted to synthesize and characterize cyclic polymers so far. 3,[18][19][20][21][22][23][24][25][26][27][28][29] The basic strategies preparing cyclic polymers are end-to-end ring closure reactions: coupling reaction between living polymers with functional groups on both ends and bifunctional linking agents 3,18,21,23,25 or intramolecular coupling reaction between chain ends of telechelic macromonomers. 26 It should be noted that cyclization products include undesired linear precursors, and dimmer and/or catanated polymers for both preparing methods.…”
mentioning
confidence: 99%
“…It is well-recognized that conventional NMR is useful to pursue chemical structure of junction point produced by cyclization reaction occurred and that matrix-assisted laser desorption/ ionization mass spectrometry (MALDI-MASS) was also applicable to analyze cyclic structures. 21,23 However, these methods are limited to a relatively low molecular weight polymer (< 10 k). Recently, liquid chromatography at the critical condition (LCCC) based on a combination of entropic and enthalpic separations has been also applied to separate a cyclic polymer from cyclic/linear mixture.…”
mentioning
confidence: 99%
“…18 -21 Throughout these experimental studies, however, the direct evidence of cyclic structure was not shown; moreover, the purity of the cyclic molecules has not been determined quantitatively in most of the works. Among them, Ohtani et al have proved the cyclic structure directly by using poly͑2-vinylpyridine͒ with detectable junction point by pyrolysis gas chromatography/mass spectroscopy and determined the ring fraction, 16 while Lee et al determined the fractions of cyclic polystyrenes precisely by liquid chromatography at the critical condition method. 17 Takano et al have reported on preparation and characterization of cyclic polystyrenes with short poly ͑2-tert-butyl-butadiene͒ sequence and proposed a novel method to prove the purity of cyclic molecule, 21 while they also prepared polystyreneblock-polyisoprene cyclic copolymers with three different compositions and determined the purity of cyclic molecules included in the samples accurately.…”
mentioning
confidence: 99%